SARA Reading Components Tests, RISE Forms: Technical Adequacy and Test Design, 2nd Edition. Issue 2 (17th September 2015) - Sabatini, John; Bruce, Kelly; Steinberg, Jonathan; Weeks, Jonathan
Abstract : This technical report describes the conceptual foundation and measurement properties of the Reading Inventory and Scholastic Evaluation (RISE). The RISE is a 6‐subtest, Web‐administered reading skills components battery. The theoretical and empirical foundations of each subtest in the battery are reviewed, as well as item designs. The results included in this report feature a vertical extension of the RISE to span Grades 5–10, psychometric analysis of parallel forms of each subtest, results of item response theory (IRT) scaling studies for each of the subtests across the entire grade span, and evaluation of differential item functioning (DIF) for gender and race/ethnicity. Abstract : Report Number: ETS RR–15–32